Latent Classes of Incarcerated People’s Behavioral Health: Differences by Childhood Adversity and Criminal History - Chassay, Lindsay (Victims & offenders, 2025)
The present study identified latent classes of incarcerated people based on indicators of their substance use and mental health. Data were used from the nationally representative 2016 Survey of Prison Inmates. Two classes of incarcerated people were identified: Non-clinical class and Clinical class. Compared to the Non-clinical class who had limited history of mental illness and limited substance use, the Clinical class had an extensive history of mental illness, substance use, and behavioral health services utilization. Moreover, the Clinical class had significantly higher prevalence of childhood homelessness, foster care, and parental incarceration and increased number of prior total arrests.